Africus : Johannesburg Biennale 95. - Ferguson, Lorna; Till, Christopher; Africus Johannesburg Biennale 1995 (Johannesburg : Transitional Metropolitan Council, 1995)
Abela, Pepe José ; Adipurnomo, Nindityo ; Admas, Mark ; Afonso, Massongui ; Ahmed, El Ghoul Ali ; Ahmed, Hassa'an Ali ; Alavanja, Nada ; Alvim, Fenando ; Amadhia, Walter ; Anatsui, El ; Antoni, Janine ; Anusapati ; Apablaza, Elias Adasme ; Arcangeli, Maurizio ; Arellano, Maria Agnes ; Armanious, Hany ; Armstrong, Geoffrey ; Arnold, Marion ; Arouff, Jeanne Gervale ; Aschieri, Guglielmo Emilio ; Avery, Eric ; Baldawoo, Teeluckdharry ; Balkenhol, Stephan ; Baloyi, Vincent ; Baqeri, Maryam ; Barker, Wayne ; Baz, Mohamed El ; Beagle, Amelia ; Belkahia, Farid ; Bellamine, Fouad ; Ben ; Benedit, Luis Fernando ; Benhura, Dominic ; Benjamin, Marcos Coelho ; van den Berg, Clive ; Bervotis, Hendrikus ; Bester, Willie ; Bickle, Berry ; Bieber, Jodi ; Bikkers, Rudolf ; Blignaut, Belinda ; Bloom, Doris ; Bogatsu, Kentse ; Boltanski, Christian ; Böröcz, András ; Boshoff, Willem ; Bostik, Vaclav ; Botha, Lien ; Boxer, David ; Breitz, Candice ; Buck, John ; Budeli, Ezekiel ; Buthelezi, Mbongeni Richman ; Cai Guo-Qiang ; Calixte, Dakpogan ; Campos, Luis ; Capalan, Carlos ; Capellan, Tony ; Carmona, Estrella ; Cavenago, Umberto ; Chandra, Mohini ; Cheifitz, Jann ; Chissano, Alberto ; Chong, Albert ; Chooramun, Dev Anand ; Christelis, Andrea ; Clain, Gilbert ; Coetzee, Neels ; Cohen, Steven ; Cookhorne, Robert ; Coppelo, Francisco ; Croft, Brenda ; Crouse, Reshada ; Cruise, Wilma ; Cullinan, Jenny ; Curling, Philippa ; Currimjee, Salim ; d'O, Honoré ; Dada, Makandal ; Daley, Leonard ; Danials, Albert ; Dausoa, Vynaud Parmessur ; David, Jacques Yves ; Deacon, Destiny ; Debaere, Hugo ; Dia, Tamsir ; Diab, Rashid ; Diba, Viye ; Dicks, Trudi ; Dikuanga, Joao Nenne ; Dime, Moustapha ; Dingler, Daniel W. ; Dlamini, Rosinah ; Dlamini, Sarah ; Donga, Muzi ; Doobah, Boopen ; etc.
biografie
Africus Johannesburg Biennale, Transitional Metropolitan Council, Johannesburg, 28 February - 30 April 1995
Engels
boek